(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This study investigates the relationship between regular physical activity and cognitive development in school-aged children. Research indicates that consistent engagement in physical exercises not only enhances physical fitness but also contributes to improved attention, memory, and problem-solving skills. A combination of observational studies, cognitive testing, and surveys was used to analyze the effects of daily physical activities on children aged 7–12. The findings suggest that structured physical education programs in schools play a crucial role in supporting both physical and cognitive growth.